International organizations - Pease, Kelly-Kate S., 1965- (Pearson custom library, 2014)
Drawing on mainstream and critical theoretical approaches, International Organizations offers a comprehensive examination of international organizations' political and structural role in world politics. The text discusses a variety of international organizations and offers the conceptual tools needed to analyze the effectiveness of their activities. Surveying key issues from international security to the environment, International Organizations looks at present and future possibilities for global governance from a broad range of perspectives.